When the Gestalt psychotherapist represents society: A facilitation experience in a special therapeutic group (Ágora de Heterodoxias, 2021)
The purpose of this experience report is, first, to describe the perceptions of a group of mothers of children with Down Syndrome of their interactions with people in the social context without accurate information about the condition; second, to understand the background configuration process in the emergence of a dialogue in which the differences between the participants and the therapist are highlighted, as a contextual phenomenon that arises from the naming of such social interactions. The group consisted of 10 women between 25 and 50 years old, with children between 1 year and 6 months and 9 years old, with no previous experience in group psychotherapy and living in the Riviera Maya in Mexico. Finally, these experiences are discussed in the light of Gestalt Therapy theorizations.
Keywords: Psychotherapy; interactive communication; intergroup relations; disadvantaged groups